2003
DOI: 10.1001/jama.289.5.579
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Risk of Stroke

Abstract: Context Observational studies suggest that heavy alcohol consumption may increase the risk of stroke while moderate consumption may decrease the risk.Objective To examine the association between alcohol consumption and relative risk of stroke.Data Sources Studies published in English-language journals were retrieved by searching MEDLINE (1966-April 2002 using Medical Subject Headings alcohol drinking, ethanol, cerebrovascular accident, cerebrovascular disorders, and intracranial embolism and thrombosis and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
502
8
27

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 802 publications
(566 citation statements)
references
References 77 publications
29
502
8
27
Order By: Relevance
“…This [EtOH] falls within the range obtained in circulation during moderate-heavy alcohol intake and of alcoholic patients with stroke-like episodes (4,27,28). In contrast to the EtOH effect, application of PSS containing either dextrose or urea (50 mM) consistently failed to evoke constriction [diameter: 105.8 Ϯ 2.2% of controls (n ϭ 4) and 98.4 Ϯ 0.7% of controls (n ϭ 4)].…”
Section: Alcohol Constricts Pressurized Cerebral Arteries By a Directsupporting
confidence: 65%
See 1 more Smart Citation
“…This [EtOH] falls within the range obtained in circulation during moderate-heavy alcohol intake and of alcoholic patients with stroke-like episodes (4,27,28). In contrast to the EtOH effect, application of PSS containing either dextrose or urea (50 mM) consistently failed to evoke constriction [diameter: 105.8 Ϯ 2.2% of controls (n ϭ 4) and 98.4 Ϯ 0.7% of controls (n ϭ 4)].…”
Section: Alcohol Constricts Pressurized Cerebral Arteries By a Directsupporting
confidence: 65%
“…Moderate-heavy drinking is associated, independently of any other factor, with an increased risk for stroke and deaths from ischemic stroke (3,4). Binge drinkers are significantly predisposed to brain hemorrhage, cerebrovascular spasm, and stroke (3,5).…”
mentioning
confidence: 99%
“…Secondly, many of the prior studies reported that alcohol consumption was an important factor contributing to the prevalence of strokes, [38][39][40] while occupation, which is one of the SES indicators, has also been found to play a crucial role in stroke prevalence. 2,4,6 However, this type of information was not available from the NHIS.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies suggest a U-or J-shaped association between moderate consumption of alcohol (one to three drinks [15-45 g alcohol] per day) and decreased risk of type 2 diabetes (41,42), coronary heart disease (CHD) (42,43), and stroke (44). However, heavy consumption of alcohol (greater than three drinks per day), may be associated with increased incidence of diabetes (42).…”
Section: Nutrition Recommendations and Interventionsmentioning
confidence: 99%